2012
DOI: 10.1055/s-0032-1315043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cytotoxic Activity of Some Brazilian Medicinal Plants

Abstract: Plants are promising sources of new bioactive compounds. The aim of this study was to investigate the cytotoxic potential of nine plants found in Brazil. The species studied were: Annona pickelii Diels (Annonaceae), Annona salzmannii A. DC. (Annonaceae), Guatteria blepharophylla Mart. (Annonaceae), Guatteria hispida (R. E. Fr.) Erkens & Maas (Annonaceae), Hancornia speciosa Gomes (Apocynaceae), Jatropha curcas L. (Euphorbiaceae), Kielmeyera rugosa Choisy (Clusiaceae), Lippia gracilis Schauer (Verbenaceae), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 29 publications
1
53
0
2
Order By: Relevance
“…Ribeiro et al (2012) tested the leaves cytotoxicity in human tumor cell lines using the thiazolyl blue test (MTT) assay and observed significant cell mortality. Despite the high mortality, the mechanism responsible for the cytotoxic activity has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al (2012) tested the leaves cytotoxicity in human tumor cell lines using the thiazolyl blue test (MTT) assay and observed significant cell mortality. Despite the high mortality, the mechanism responsible for the cytotoxic activity has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 1). Investigating specifi c tumors (colon carcinoma, melanoma, glioblastoma and leukemia promielocitic), RIBEIRO et al (2012) reported that mangaba would not be active. This does not mean that the extract of mangaba is also inactive for other/ all forms of tumor.…”
Section: Resultsmentioning
confidence: 99%
“…This does not mean that the extract of mangaba is also inactive for other/ all forms of tumor. While RIBEIRO et al (2012) used leaves, branches, fruit and latex, this study used the whole mature. Furthermore, the process of extraction and concentration used were different, which may have affected the concentration of active substances.…”
Section: Resultsmentioning
confidence: 99%
“…Extracts of Annona pickelli and Annona salzmannii did not show any expressive antiproliferative effect. In these species, it seems therefore that associations of compounds or the minor compounds are responsible for their cytotoxic activity [22]. The presence of acetogenins identified as the major constituents of some Annonaceae species could explain the anticancer activity observed for Annona crassiflora and Xylopia aromatica [23].…”
Section: Discussionmentioning
confidence: 99%